The responsibility of the state and the calling of the church in the South African context of crime and violence – a theological investigation - Wyk, J. H. van (Koers, 2005)
This article investigates not only the complex relation between church and state, but also the general and particular responsibilities of the state towards crime and violence. In this regard attention is also paid to the calling and task of the church. The conclusion arrived at is rather alarming in that the moral situation in South Africa has reached a nadir such that the state and the church – each in its own way – has to broach the challenge with great urgency. On the one hand crime and violence should be brought back to “normal” proportions, while on the other hand, South Africa is in desperate need of a new moral orientation and a new culture of respect for human life and the possessions of others.